Biorthognal, Symlet & Discrete Meyer Wavelet Based Palm Print Recognition System - Manjunath, M (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2018)
The proposed work investigates the different wavelets at feature level for Palm print based recognition using an indigenously developed peg-free image acquisition platform. The results depict the superiority of different wavelets for the Palm print recognition, using coarse level information. The recognition rate for the proposed model is 97.5% and the value of FRR and FAR is 0.05 and 0.05 respectively. Use other transformer for processing to improve the performance of matching algorithm. Also use best method to perform recognition process.